Maria Borowiecka - unfinished biography - Tadeusz Aleksander (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2014)
The paper presents a brief biography of Maria Borowiecka (born in 1875), the social and educational activist of the inter-war period, particularly devoted to the education of adults. It refers to her social origins; mentions her academic titles in Mathematics, Physics and Educational Sciences; includes the names of her eminent teachers. Maria Borowiecka is depicted as a long-term teacher, who was engaged also in courses and schools for adults; an author of textbooks and other didactic materials; a coordinator of didactic work of teachers in adult education, who enjoyed a lot of successes in constructing theories in that field. A substantial part of the study is devoted to her most influential work under the following title: Kształcenie dorosłych. Próba dydaktyki. At the end there is an appeal for the completion of Borowiecka's biography, still full of many gaps, which unequivocally proves that despite the industrious search by the author of this paper for facts relating to the last years of Borowiecka's life and the date of her death, the endeavours to fill these gaps have been ineffective so far.